APLIKASI THEORY OF PLANNED BEHAVIOR DALAM MENJELASKAN PERILAKU EKOLOGIS GENERASI Y DI KOTA DENPASAR - Suryandari, Ni Ketut Dian; Suprapti, Ni Wayan Sri; Sukaatmadja, I Putu Gde (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016)
This research aimed to examine the effect of environmental knowledge on environmental attitude;the effect of environmental attitudes, subjective norms, and perceived behavioral control on ecological behavior; and the diference of environmental knowledge, environmental attitudes, and ecological behavior between male and female. Data collected through questionnaires distributed to 120 respondents in some nutrients club in Denpasar City determined by purposive sampling. Hypothesis tested by using Partial Least Square and t-test. The results indicate that the environmental knowledge has positive and significant effect on environmental attitude; environmental attitudes, subjective norms, and perceived behavioral control have positive and significant effect on ecological behavior; and there is no significant difference in environmental knowledge, environmental attitude and ecological behavior between Generation Y male and female in Denpasar City.
Keywords: environmental knowledge, environmental attitudes, ecological behavior, Theory of Planned Behavior